Effects of structured and unstructured interventions on fundamental motor skills in preschool children: a meta-analysis - Chen, Delong; Zhao, Guanggao; Fu, Jinmei; Shun, Sunli; Su, Liqiang; He, Zihao; Chen, Ruiming; Jiang, Tianle; Hu, Xuewen; Li, Yunong; Shen, Fanchao (Frontiers in Public Health, 2024)
Background It has been suggested that higher levels of fundamental motor skills (FMS) promote the physical health of preschool-aged children. The impacts of structured and unstructured interventions on FMS in children aged 10–16 years have been widely acknowledged in previous studies. However, there is a lack of relevant studies in preschool-aged children. Objective This meta-analysis aimed to compare the effects of structured and unstructured interventions on FMS in preschool-aged children. Methods The PubMed, Web of Science, and Google Scholar databases were searched from inception to 1 November 2023 to identify experiments describing structured and unstructured interventions for FMS in preschool-aged children. The Downs and Black Checklist was used to assess the risk of bias. A random effects model was used for the meta-analysis to evaluate the pooled effects of interventions on FMS. Subgroup analyses based on the duration and characteristics of the intervention were conducted to identify sources of heterogeneity. Results A total of 23 studies with 4,068 participants were included. There were 12 studies examining structured interventions, 9 studies examining unstructured interventions, and 6 studies comparing structured vs. unstructured interventions. The risk of bias in the included studies was generally low. All interventions significantly improved FMS in preschool-aged children compared to control treatments (p < 0.05). Structured interventions had more significant effects on locomotor skills (LMSs) in preschool-aged children than unstructured interventions (Hedges’ g = 0.44, p = 0.04). The effects of structured interventions were strongly influenced by the total intervention duration, such that long-term interventions were more effective (Hedge’s g = 1.29, p < 0.001). Conclusion Structured interventions play a crucial role in enhancing FMS among young children, especially when considering LMSs. These interventions require consistent and repeated practice over time to reach proficiency. Systematic review registration: PROSPERO, identifier number CRD42023475088, https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42023475088.